STRUKTUR PASAR DAN KEDUDUKAN INDONESIA PADA PERDAGANGAN TUNA OLAHAN DI PASAR DUNIA, JEPANG DAN USA - Sri Hidayati (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2014)
The aim of this research were to knowing structure of the market and knowing Indonesia’s status as preserved tuna’s exporter in word markets, which are Japan and USA. Trough this research, researchers would showed the competitveness of preserved tuna’s trading in the world either Indonesia’s export destination. This research used time series data from 1989 until 2012. The analysis methods were Herfindahl Index (HI) and Concentration Ratio (CR4). The result of this research showed that : (1) Indonesia is an exporter remain either main exporter on preserved tuna’s trading in Japan and USA as world market, (2) preserved tuna’s market structure in Japan and USA as world market leaded to monopoly. Keywords : preserved tuna’s, structure of the market